An Overview of the Concentration of Natural Radionuclides Present in the Iraqi Environment: A Review (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
This research conducts a comprehensive literature analysis on the topic of Iraq, specifically examining the evaluation of radioactive activity in seventeen cities and the assessment of the nuclear site environment. A systematic review of the literature and scientific studies on estimating the concentration level of naturally occurring radionuclides in soil and water were carried out using a gamma ray spectrometer system and the RAD-7 device.. The results generally indicate that the natural level of radioactivity and radon in soil and water samples from the examined areas fall within the internationally permissible range. However, many areas, such as Basra, Sulaymaniyah, and the area around the thermal Al-Dura station in Baghdad, suffer from high radon levels, indicating potential locations that require attention. The research sites exhibited a comparatively lower average concentration of 238U and 232Th compared to reported calculations in numerous countries and the global average range recommended by the United Nations Scientific Committee on the Effects of Atomic Radiation in 2017. With the increase observed at the average concentration of 40K, was found that the concentrations of radionuclides in water samples collected from several cities in Iraq were lower than international standards, except in the cities of Sulaymaniyah, Karbala, Mosul, and Najaf. The overall average level of radionuclides in water was discovered to be less than the level stated in other countries.